Basiliximab with delayed introduction of calcineurin inhibitors as a renal‐sparing protocol following liver transplantation in children with renal impairment. (30th September 2013) - Mouzaki, M.; Yap, J.; Avinashi, V.; Babu, A.; Fu, A.; Deangelis, M.; Van Roestel, K.; Ghanekar, A.; Kamath, B.; Avitzur, Y.; Fecteau, A.; Jones, N.; et al.
Abstract: Renal impairment is frequently compromised in patients with end‐stage liver disease and is associated with increased long‐term mortality post‐LT. In contrast to CNI, basiliximab is an immunosuppressive agent with minimal nephrotoxic potential. This study reviews the experience of a single pediatric liver transplant center's renal‐sparing approach with the use of basiliximab and MMF to compensate for delayed entry of CNI in children with renal impairment at the time of organ availability. There were no differences in renal function between pediatric patients with and without pre‐LT renal impairment within the first year (cGFR: 135 mL/min/1.73 m 2 vs. 144 mL/min/1.73 m 2 ; p = 0.56) or at 5–8 yr following LT, (129 mL/min/1.73 m 2 vs. 130 mL/min/1.73 m 2 ; p = 0.97). In addition, there was no difference in ACR rates (50% vs. 43%, p = 0.62) between patients in the basiliximab group and those patients receiving standard CNI and steroid strategies. The utilization of a renal‐sparing approach with basiliximab alongside delayed entry and lower early target trough levels of CNI in children with renal impairment at the time of LT is safe and maintains excellent long‐term kidney function.